Dynamical evolution of Schumann resonance spectra during a strong Q-burst on July 11, 2004 - ŠEVČÍK, Sebastián; KOSTECKÝ, Pavel; KOHÚT, Igor; TURŇA, Ľubomír (Contributions to Geophysics and Geodesy, 2021)
During permanent monitoring of Schumann resonances, numerous Q-bursts (strong transient ELF signals) were observed. In early morning of July 11, 2004, a very strong Q-burst was recorded and it was possible to analyze the dynamical evolution of electric field component spectra. The time evolution of the signal, together with dynamical behavior of frequency spectrum, enables to make conclusion about the spatial distribution of the field in the Earth-ionosphere resonator.